Increased oestradiol in hepatitis E virus‐infected pregnant women promotes viral replication. Issue 6 (27th February 2018) - Yang, C.; Yu, W.; Bi, Y.; Long, F.; Li, Y.; Wei, D.; Hao, X.; Situ, J.; Zhao, Y.; Huang, F.
Summary: Hepatitis E virus (HEV) infection causes subclinical diseases, leading to high mortality (>25%) in pregnant women. HEV replication is aggressively escalated in pregnant women, especially in the third trimester of pregnancy. Oestrogen plays an important role in pregnancy. However, the pathogenesis of HEV in pregnant women or immunosuppressive pregnant women (such as HIV‐infected or organ‐transplanted pregnant women) remains unclear. We investigated the role of oestradiol in HEV infection in a cell culture system. HEV‐infected pregnant women had significantly higher oestradiol levels compared with uninfected individuals. HEV infection was significantly increased in cells treated with analogues of oestradiol, diethylstilbestrol (DES) or 17β‐oestradiol in a dose‐dependent way. However, tamoxifen, an antagonist oestrogen, inhibited HEV replication. HEV infection inhibits oestrogen receptor (ER‐α) expression. Immunofluorescence and co‐immunoprecipitation assays indicated that ER‐α interacted with the helicase of HEV ORF1 indirectly. More importantly, HEV infection was exacerbated in immunosuppressive cells treated with an inhibitor of PI3K‐AKT‐mTOR signal pathway (LY296004) and supplemented with pregnant women serum with high oestradiol simultaneously. These results strongly suggest that pregnant women with high oestradiol and/or immunosuppression will be vulnerable to HEV infection.